2021
DOI: 10.1515/cclm-2021-0208
|View full text |Cite
|
Sign up to set email alerts
|

A new tool for sepsis screening in the Emergency Department

Abstract: Objectives In this study, we developed and evaluated the diagnostic accuracy of the Sepsis Index for early sepsis screening in the Emergency Department (ED). Methods Sepsis Index is based on the combination of monocyte distribution width (MDW) and mean monocyte volume (MMV). Sepsis Index≥1 was selected to define sepsis. We tested its diagnostic accuracy in an ED population stratified in four groups: controls, Systemic Inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…Using the previously established decisional cut-off values of 23 and 1 for the MDW and SI, respectively [ 13 , 16 ], we found out that, in this validation cohort, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (LR+) and negative likelihood ratio (LR-) for sepsis were, respectively, 0.79 (MDW) vs. 0.79 (SI), 0.84 vs. 0.91, 0.27 vs. 0.38, 0.98 vs. 0.98, 5.08 vs. 8.52 and 0.25 vs. 0.23.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the previously established decisional cut-off values of 23 and 1 for the MDW and SI, respectively [ 13 , 16 ], we found out that, in this validation cohort, the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (LR+) and negative likelihood ratio (LR-) for sepsis were, respectively, 0.79 (MDW) vs. 0.79 (SI), 0.84 vs. 0.91, 0.27 vs. 0.38, 0.98 vs. 0.98, 5.08 vs. 8.52 and 0.25 vs. 0.23.…”
Section: Resultsmentioning
confidence: 99%
“…The MDW was measured on whole-blood venous samples collected in K3-EDTA tubes on the UniCel DxH 900 haematology analyser (Beckman Coulter, Inc., Brea, CA, USA) within 2 h from the collection, as recommended by the manufacturer, after the laboratory analysis ordered by the ED clinicians were completed. The SI was calculated for each patient by applying the formula based on the values of the MDW and MMV, as previously described [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been approved by the Food and Drug Administration (FDA) as a biomarker for the early detection of sepsis in ED. Recently, several authors showed that MDW has good diagnostic accuracy for early-identifying patients at high risk of developing sepsis, especially in the ED and the ICU [114][115][116][117][118][119][120][121][122][123]. MDW is characterized by a high negative predictive value for sepsis diagnosis.…”
Section: Monocyte Distribution Widthmentioning
confidence: 99%
“…Based on morphological changes in monocytes during inflammation, the sepsis index ((SI), based on MDW and mean monocyte volume (MMV)) significantly improves the accuracy of early sepsis screening and diagnosis. 28 , 29 A blind, prospective cohort study was conducted in two different emergency departments at Ohio State University by Crouser et al, 30 1320 subjects were enrolled in the ED consecutively. Those patients were grouped into systemic inflammatory response syndrome (SIRS), infection, and sepsis (including sepsis, severe sepsis, and septic shock) groups, and MDW was measured using a UniCel DxH 800 analyzer.…”
Section: Introductionmentioning
confidence: 99%